Analysis of Carbon Above The Ground As The Indicator of Forest Health In Protection Forest Registers 25 - Lestari, Rayi Nindya; Wulandari, Christine; Darmawan, Arief; Safe’i, Rahmat (Journal of Sylva Indonesiana, 2019)
Forest health is very important in the whole world, when global issues such as air pollution, acid rain, forest fires, quality and quantity of water, and global climate change has affected the realization of a sustainable forest. Achievement of forest preservation in a forest ecosystem, criteria and indicators have been widely formulated. Therefore, carbon analysis is significantly needed to figure the indicator of forest health. The aim of the research was to analyze the carbon as a forest health indicator in Protection Forest, Reg. 25. The data were collected through cluster plot based on Forest Health Monitoring (FHM) method. The calculus of the amount of stored biomass within the tree was referring to Ketterings, et al, (2001) is W = 0,11 x Ï x D2,62, mean while under growth and litter biomass are gained from total dry weight. Carbon sink is based on conversion number; 0,5 out of total biomass number. The average of carbon stored in Protection Forest Reg. 25 is about 939,12 ton/ha. Carbon within the stands are contributed the most; 937, 43 ton/ha, litter carbon about 1,06 ton C/ha and undergrowth carbon is about 0,63 ton C/ha. Based on the analysis, carbon can be a health indicator of Protection Forest Register 25 with the category of ugly, moderate, and good. Cluster plots 1 and 2 included good category (1,232.75 ton C/ha -- 1744.13 ton C/ha). As for cluster plots 3 and 4 included ugly category (209.97 ton C/ha -- 721.35 ton C/ha).